PEMBIASAAN ORANG TUA MENANAMKAN PENDIDIKAN ISLAM PADA ANAK REMAJA DI KELURAHAN MANGGA KECAMATAN MEDAN TUNTUNGAN - Fathis Silmi Ramadani; Junaidi Arsyad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the habit of parents to instill Islamic education in adolescents in Mangga village. The research method uses qualitative and descriptive methods. The data was taken through observation, interviews, and documentation. Data analysis, using the miles and huberman techniques, namely, data retrieval, data presentation, and conclusion drawn. The findings obtained were motivated by the existence of problems that occurred in the field, that teenagers in Mangga village have bad habits, this triggered serious problems, so it requires special attention to every parent and family at home. Therefore, parents begin to accustom children from childhood to carry out positive activities, support, instill strong Islamic values and pay special attention to every child, especially teenagers, both from the influence of the environment, digital media, and adolescent associations.